Work with Young People : Theory and Policy for Practice. - Wood, Jason (Sage Publications, 2009)
The book covers a fascinating range of theory, policy and practice research not covered elsewhere in one text. The editors are to be congratulated' - Marian Charlton, Leeds Metropolitan University. 'The book offers a broad overview of the issues and literature, and will be of immediate use. It enables students to bring themselves up to date with contemporary concerns and changes in the field of community and youth work' - Jean Spence, University of Durham. This authoritative text is a must-read for anyone working - or training to work - with young people. It considers how theory, policy and pr.